Evaluation of a nanoparticle drug delivery vehicle in medulloblastoma and organotypic brain cell cultures - Meng, Weina (2006)
It has been widely reported that cell culture dimension and microenvironment influence cell proliferation, differentiation, and gene expression, which lead to different interactions between drug delivery systems and cells. The development in evaluation of drug delivery systems has reached the stage where investigations are now concentrating on intracellular uptake and subcellular localization of drug delivery systems.This thesis investigates the use of three-dimensional (3-D) tissue culture models to study how nanoparticles (NPs) may behave in vivo. Poly (glycerol-adipate) (PGA) NPs can degrade into glycerol and adipate, which are not having toxic and anyundesirable local or systemic effects in the host. Following on the initial physicochemical characterization of PGA NPs loaded with drug and fluorescent dyes, investigations moved on to the biological studies of NPs in various cell culture model, e.g. monolayer culture, 3-D culture models, and brain tumour invasion model. Particle size, surface charge, and hydrophobicity are important features affecting the amount of particles taken up by cells and intracellular localisation of particles. Thus, the physicochemical properties of drug and fluorescent dye loaded PGA NPs were assessed by Photon Correlation Spectroscopy, Laser Doppler Anemometry, and drug/fluorescent dye loading studies. These studies indicated that physicochemical properties of drug, fluorescent dyes and PGA polymer could influence drug /fluorescent dye loading, which results in different particle size and surface charge of PGA NPs. Quantitative and qualitative investigations into the influence of cell culture dimension on uptake of NPs by cells, both by confocal fluorescence microscopy and flow cytometry, revealed that DAOY cells took up NPs more effectively when in 3-D spherical aggregate culture than in 2-D monolayer culture while uptake of NPs by normal brain cells was lower in 3-D cell culture than that seen in 2-D monolayer culture. This resulted in intracellular fluorescence intensity about 6 times higher in DAOY aggregates than normal brain cell aggregates while in monolayer culture mixed brain cells took up 2 times as many NP as the DAOY cells. The results from studies of NPs migrating through aggregates and tissue slices also indicated that penetration ofNPs in 3-D culture models was affected by the structure of the interstitial compartment and composition of extracellular matrix. Microscopic investigation of the histology of a co-culture invasion model of DAOY aggregates and a organotypic brain slice confirmed that DAOY cells massively invaded into cerebellum slices after a 4-day co-culture while the invasion of DAOY cells were limited within cerebral cortex slices even after a 6-day co-culture. Selective uptake of NPs by host cells and brain tumour cells were also assessed in this 3-D brain tumour invasion model. It showed that most NPs were taken up by DAOY cells instead of brain cells.